Profetika Hukum Keluarga Islam Dalam UU Tindak Pidana Kekerasan Seksual - Mohsi Mohsi (HKI IAI Miftahul Ulum Pamekasan, 2022)
Sexual harassment is unwanted sex-related approaches, including requests for sex, and other behavior that verbally or physically refers to sex. Sexual violence is an important topic that needs to be solved, given the high rate of sexual violence from year to year. The Law on the Elimination of Sexual Violence is a way that is expected by the Indonesian people as an umbrella of law and rule of law to take action against all forms of sexual crimes that plague Indonesian citizens. in this study tries to analyze the urgency and relevance of these rules for the development of law in Indonesia. reviewing regulations from the prophetic aspects of Islamic law and the reconstruction of Islamic law, as well as the spirit of legal moderation and responding to current issues related to forms of violence that befall society, especially children and women.